Spending and Utilization on Drugs Prescribed by Otolaryngologists to Medicare Beneficiaries, 2013 to 2017. (September 2022) - Shah, Shivani A.; Miller, Lauren E.; Xiao, Roy; Workman, Alan; Xu, Lucy; Rathi, Vinay K.
Objectives: The significant and rising cost of prescription drugs is a pressing concern for patients and payers. However, little is known about spending on and utilization of drugs prescribed by otolaryngologists. Methods: Utilizing publicly available Medicare Part D Prescriber Public Use data, we conducted a retrospective cross-sectional analysis of 34 small-molecule drugs commonly prescribed by otolaryngologists (defined as 2017 Medicare Part D spending ≥500 000) to Medicare beneficiaries. Prescription data was characterized by drug type (brand name vs generic). Primary outcomes for each prescription drug included the total annual cost and the total annual number of days supplied. Results: From 2013 to 2017, spending on drugs prescribed by otolaryngologists to Medicare beneficiaries decreased by 32.1 million (131.7–99.5 million; relative decrease 24.4%; compound annual growth rate [CAGR] −5.4%), while total utilization increased by 24.9 million days supplied (74.6–99.5 million; relative increase 33.3%; CAGR 5.9%). For brand name drugs, there was a decrease in spending (71.1–26.7 million; relative decrease −62.4%; CAGR −17.8%) and utilization (11.2–3.1 million days supplied; relative decrease −72.5%; CAGR −22.8%). In contrast, generic drugs demonstrated increased spending (60.6–72.8 million; relative increase 20.2%; CAGR 3.7%) and utilization (63.5–96.4 million days supplied; relative increase 51.9%; CAGR 8.7%). Conclusions: Spending on drugs prescribed by otolaryngologists to Medicare Part D beneficiaries declined between 2013 and 2017 in part due to a transition from brand name drugs to lower-cost generic equivalents.